Peningkatan kemampuan guru kelas dalam Penyusunan RPP berbasis pendekatan saintifik melalui Supervisi akademik MIN 1 Aceh Tenggara - Darmayanti, Sri (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The problem in this School Action Research (PTS) is the understanding of classroom teachers in the preparation of the 2013 Curriculum RPP is still far from expectations. There are several things that be-come obstacles including: (1) The creativity and innovation of classroom teachers is relatively low; (2) Teachers still adopt the example RPP from KTSP 2006; where there are still competency standards found in the content standards not in the syllabus; (3) Learning objectives have not been arranged logi-cally; (4) the flow of the learning implementation plan prepared has not been based on a scientific ap-proach and has not shown the stages of exploration, elaboration and confirmation activities, so that the lesson plans are made less meaningful; and (5) An authentic assessment plan is not yet visible, and so on. This requires efforts to improve the quality, guidance, motivation and direction of the School Princi-pal. This study intends to describe the efforts to improve the ability of MIN 1 grade teachers in South-east Aceh as many as 3 representatives of class teachers in preparing Learning Implementation Plan (RPP) Based on Scientific Approaches through academic supervision activities. Academic supervision is a coaching model conducted by the Principal to the teacher to help solve problems related to learning activities so that the quality of learning can be achieved optimally. Madrasah Action Research (PTM) includes quantitative research using Comparative Descriptive Analysis by comparing the results of the initial conditions with the results of Cycle I local level upgrading techniques (In House Training) and the results of Cycle II with personal conversation techniques. The procedures performed in this study in-clude planning, implementing actions, observations and reflections that are recycled or cyclical. This research was conducted in two cycles. The average quality of RPP Based on Scientific Approach in Pre-Cycle conditions was 71.66 (less category). The average quality of RPP Based on Scientific Approach in Cycle I was 86.33 (good category). Increased results of Cycle I compared to initial conditions was 18%. While the average quality of RPP Based on Scientific Approach in Cycle II is 98.66 (very good catego-ry). The increase in the results of Cycle II compared to the results of Cycle I was 12.33%. Thus, aca-demic supervision can improve the ability of MIN 1 Aceh Tenggara class teachers in the preparation of a lesson plan based on a scientific approach significantly.